Utilization of struvite recovered from high-strength ammonium-containing simulated wastewater as slow-release fertilizer and fire-retardant barrier. Issue 2 (15th January 2020) - Yetilmezsoy, Kaan; Kocak, Emel; Akbin, Havva Melda; Özçimen, Didem
ABSTRACT: Sustainable uses of the struvite (magnesium ammonium phosphate hexahydrate, MgNH4 PO4 ·6H2 O, MAP) recovered from the synthetic wastewater, as a high-quality slow-release fertilizer for the growth of nine medicinal plants and a fire-retardant barrier on the flammability of cotton fabric and wooden plate, were explored in this study. The previous experimental results demonstrated that under the optimal conditions, about 98.7% of NH 4 + − N (initial NH 4 + − N = 1000 mg/L) could be effectively and successfully recovered from simulated wastewater in the form of MAP precipitate. Rates of increase in total fresh weights, total dry weights, and fresh heights of plants grown in soil fertilized with the struvite were determined as 67%, 52%, and 12% for valerian; 121%, 75%, and 18% for cucumber; 421%, 260%, and 47% for dill; 314%, 318%, and 27% for coriander; 432%, 566%, and 30% for tomato; 285%, 683%, and 26% for parsley; 200%, 225%, and 9% for basil; 857%, 656%, and 92% for rocket; and 146%, 115%, and 28% for cress, respectively, compared to the control pots. The microstructure, elemental composition, surface area, thermal behaviour, and functional groups of the grown crystals were characterized using SEM, EDS, BET, TGA-DTG-DSC, and FTIR analyses, respectively. Flammability tests and thermal analyses concluded that the dried and crumbled/implanted form of struvite used as a fire-retardant barrier demonstrated a remarkable flame-resistant behaviour for both cotton fabric and wooden plate. Findings of this experimental study clearly corroborated the versatility of struvite as non-polluting and environmentally friendly clean product for the sustainable usage in different fields GRAPHICAL ABSTRACT: